STRATEGI KOMUNIKASI DAKWAH BANG KEVIN MELALUI MEDIA TIKTOK - Alan Kiffani, Ilman Zuhar; Fajrul Islam, Ahmad Fakhruddin (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2023)
This article describes the important role of da'wah in technological developments in the millennial era. Bang Kevin is a Tiktok account that is in the da'wah category, this can be concluded because there are many videos containing da'wah messages packaged in millennial and interesting language, so that most other Tiktok users can understand and accept them, namely young people to adults. This study aims to find out how Kevin Kausar's universal da'wah strategies and techniques are in Bang Kevin's TikTok account. This study uses a qualitative approach while the method used by researchers is descriptive analysis "Bang Kevin's Universal Da'wah Communication Strategy Through TikTok Media". In this study, descriptive analysis is very relevant for understanding and describing the da'wah communication strategies and techniques used by Kevin Kaustar through the Bang Kevin TikTok account. The results of the study show that the communication strategy carried out by Kevin Kautsar is by using a mass communication strategy in which Kevin Kautsar uses social media in conveying da'wah messages. The mass communication strategy is carried out using the application of interpersonal communication strategy theory which is more inclined towards the importance of understanding and positioning oneself with the audience as explained by Kevin Kautsar about the importance of understanding the facts and problems experienced by society so that they can find and convey solutions. Thus it can attract the attention of netizens which is the main goal in conveying da'wah messages. After the attention of the public or netizens can be achieved, communication rules are implemented which convey da'wah messages with good and appropriate techniques such as Qaulan Sadidan, namely using correct and good speech, using the Qaulan Baligha rules, conveying communication messages precisely and straightforwardly according to the context conveyed and Qaulan Layina which means gentle talk. Researchers argue that preaching strategies need to be studied so that they can be accepted by the wider community from all walks of life.